VOICE DISORDERS AMONG TEACHERS IN SLOVENIA: PREVALENCE AND SOME RISK FACTORS - Tanja Soklič; Irena Hočevar Boltežar (Zdravniški Vestnik, 2004)
Background. Teachers as voice professionals with heavy vocal load represent a population at high risk of vocal problems. Until now there has not been any study evaluating prevalence and risk factors for voice disorders among teachers in Slovenia. Methods. Questionnaires about voice disorders and vocal habits were sent to randomly chosen 10% of elementary, middle schools and kindergarten in Slovenia. Answers from 1509 completed questionnaires were analyzed by statistical program SPSS 11.0. Results. In the school year 2002/03 51% of teachers occasionally experienced voice disorders and 15% did frequently. The prevalence of transient voice problems was therefore about 66%. By univariate χ 2 test we found statistically significant relationship to frequent voice disorders for female sex (p < 0.02), middle school teachers (p < 0.02), age over 40 years (p < 0.0005) and atopic constitution (p < 0.006); voice disorders during study showed borderline significance (p < 0.07). There was no significant relationship to voice problems for yelling, talking loudly or rapidly, using chalk while talking, cigarette smoking, water intake and gastroesophageal reflux. Statistically significant variates were included in the multivariate logistic regression model. There was 1.9-times higher risk of experiencing frequent voice disorders in females than for males (p < 0.003). Risk of vocal problems in middle school teachers was 1.5-times higher than in kindergarten teachers (p < 0.01) and 1.8-times higher than in elementary school teachers (p < 0.0005). Age over 40 years carried 2,3-times higher risk for hoarseness than age under 40 years (p < 0.0005). Voice disorders during study showed 1.7-times higher risk for later occupational vocal problems (p < 0.02). Atopic constitution had 1.6-times higher risk for frequent vocal problems (p < 0.008). The questionaire also showed how unfamiliar to vocal hygiene Slovene teachers are. Conclusions. The prevalence of voice disorders among teachers in Slovenia is high – about 66%. In our opinion the teaching of right vocal technique, vocal hygiene, prevention and therapy of voice disorders should be included in the study for the future vocal professionals. Before entering study vocal constitution of candidates should be evaluated.